Differential gene expression according to race and host plant in the pea aphid. Issue 17 (26th August 2016) - Eyres, Isobel; Jaquiéry, Julie; Sugio, Akiko; Duvaux, Ludovic; Gharbi, Karim; Zhou, Jing‐Jiang; Legeai, Fabrice; Nelson, Michaela; Simon, Jean‐Christophe; Smadja, Carole M.; Butlin, Roger; Ferrari, Julia
Abstract: Host‐race formation in phytophagous insects is thought to provide the opportunity for local adaptation and subsequent ecological speciation. Studying gene expression differences amongst host races may help to identify phenotypes under (or resulting from) divergent selection and their genetic, molecular and physiological bases. The pea aphid ( Acyrthosiphon pisum ) comprises host races specializing on numerous plants in the Fabaceae and provides a unique system for examining the early stages of diversification along a gradient of genetic and associated adaptive divergence. In this study, we examine transcriptome‐wide gene expression both in response to environment and across pea aphid races selected to cover the range of genetic divergence reported in this species complex. We identify changes in expression in response to host plant, indicating the importance of gene expression in aphid–plant interactions. Races can be distinguished on the basis of gene expression, and higher numbers of differentially expressed genes are apparent between more divergent races; these expression differences between host races may result from genetic drift and reproductive isolation and possibly divergent selection. Expression differences related to plant adaptation include a subset of chemosensory and salivary genes. Genes showing expression changes in response to host plant do not make up a large portion of between‐race expression differences, providing confirmation of previous studies' findings that genes involved in expression differences between diverging populations or species are not necessarily those showing initial plasticity in the face of environmental change.